Author Correction: Comparable antibacterial effects and action mechanisms of silver and iron oxide nanoparticles on Escherichia coli and Salmonella typhimurium - Lilit Gabrielyan (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.